Engineering twin structures and substitutional dopants in ZnSe0.7Te0.3 anode material for enhanced sodium storage performance - Jingui Zong; Yazhan Liang; Fan Liu; Mingzhe Zhang; Kepeng Song; Jinkui Feng; Baojuan Xi; Shenglin Xiong (Nature Communications)
Abstract Compared with lithium-ion batteries (LIBs), sodium-ion batteries (SIBs) are an alternative technology for future energy storage due to their abundant resources and economic benefits. Constructing various defects is considered to be a common viable means of improving the performance of sodium storage. However, it is of significance to thoroughly scrutinize the formation mechanism of defects and their effects and transition during the charge–discharge process. Here, twin structures are introduced into ZnSe0.7Te0.3 nanocrystals by doping of Te heteroatoms. The Te dopants are visualized to locate in the lattices of ZnSe by spherical aberration electron microscopy. The formation of twin structures is thermodynamically promoted by Te heteroatoms partially replacing Se based on the theoretical calculation results. Moreover, calculation results show that with the increase of twin boundaries (TBs), the sodium diffusion energy barrier is greatly reduced, which helps the kinetics of sodium ion diffusion. In the connection, the composition and amount of TBs are optimized via tuning the doping level. The combined effect of point defects and twin structures greatly improves the sodium storage performance of ZnSe0.7Te0.3@C. Our work reveals the mechanism of the point defect on the twin plane defect and systematically investigates their effect on the electrochemical performance.